Environmental and Social Management Plan (ESMP) for the Installation of Soil Archive Equipment and Gas Chromatograph in Ibadan, Nigeria - International Institute of Tropical Agriculture (IITA) (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This Environmental and Social Management Plan (ESMP) has been developed for the installation of a Soil Archive System and a Gas Chromatograph (GC) at the International Institute of Tropical Agriculture (IITA) in Ibadan, Nigeria, under the Additional Financing (AF) of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. The ESMP clarifies (i) the mitigation measures to be undertaken during the planning, installation, and operational phases to eliminate or reduce environmental and social (E&S) risks to acceptable levels, and (ii) the actions required to ensure that these measures are implemented effectively.